Fifth Five Year Plan Uttar Pradesh Draft Annual Plan 1976-77 Vol. II Uttar Pradesh - Planning Commission (Planning Commission, 1976)
To cater to the needs of a large number of children in the age-group 11—14 who have not been to the school and to remove the wastage and stagnation at the elementary stage caused mainly by economic pressure, a programme of nonformal part-time education for the children in the age-group 11—14 has been introduced in 1975. Thirty-five part-time classes have been started in each district. Books and stationery are provided free of cost in these classes.
Uttar Pradesh Planning Department
Uttar Pradesh Planning Department